DEVELOPMENT OF PHYSIC LEARNING ANIMATION MEDIA USING ADOBE FLASH CS5 - Amirullah A. Gere; Bq. Azmi Syukroyanti; Saiful Prayogi (Universitas Pendidikan Mandalika, 2016)
This research aims to develop a medium of learning physics animation using Adobe Flash CS5 software on the subject of momentum and impulse. Testing the feasibility of learning through the media trial on 2 validator, ie material experts and design media. This study using ADDIE development model, namely Analysis, Design, Development, Implementation, Evaluation. This study only uses three stages, namely until the stage of development of animation media learning software designed using Adobe Flash CS5. Validation matter experts on media appearance and suitability of materials with the acquisition of a score of 3.6 that is rated